Novel activity-based probes for N-acylethanolamine acid amidase. Issue 86 (16th October 2017) - Petracca, Rita; Romeo, Elisa; Baggelaar, Marc P.; Artola, Marta; Pontis, Silvia; Ponzano, Stefano; Overkleeft, Herman S.; van der Stelt, Mario; Piomelli, Daniele
Abstract : Two NAAA activity-based probes were generated as tool for the identification of new inhibitors and the investigation of NAAA physiology. Abstract : The cysteine hydrolase, N -acylethanolamine acid amidase (NAAA) is a promising target for analgesic and anti-inflammatory drugs. Here, we describe the development of two unprecedented NAAA-reactive activity-based probes as research tools for application in the discovery of new inhibitors and for the in-depth characterization of NAAA in its cellular environment.